The tax consequences of a contingent liability disposed of as part of the sale of a business as a going concern - Staude, Daylan (Rhodes University, Faculty of Commerce, Department of Accounting, 2015)
The sale of an entity as a going concern has a number of tax consequences for both the purchaser and the seller. The tax deductibility of a contingent liability upon its transfer from the seller to the purchaser, where the selling price has been reduced by the value of the contingent liabilities transferred, remains uncertain following the decision in Ackermans Ltd v Commissioner for the South African Revenue Service. An expense is either deductible under a specific section of the Income Tax Act, 58 of 1962, or under the general expense provisions in terms of sections 11(a) and 23(g). The Act does not contain a specific section relating to contingent liabilities and therefore a contingent liability will need to be considered for deduction under these sections. The Act further disallows an expense as a deduction under section 23(e), where a reserve is created (for example a leave pay provision). This study analyses the tax deductibility of a contingent liability, where the contingent liability has been transferred from the seller to the purchaser in a sale of an entity as a going concern and the purchase price has been reduced to compensate for the transfer of the contingent liability. The deductibility of the contingent liability was first assessed in terms of the provisions of the Act (sections 11(a), 23(g) and 23(e)) and associated case law. The decision in the Ackermans case and its preceding Income Tax Case 1839 was then analysed in order to establish the principles arising from the decisions. Finally the proposals in the Draft Taxation Laws Amendment Bill, 2011, and the subsequent Discussion Document issued by the South African Revenue Service were discussed. The analysis revealed the continuing confusion surrounding the status quo, thus demonstrating the importance of legislative intervention to provide guidelines for taxpayers.
Keywords: Sale of business enterprises -- Taxation -- South Africa; Sale of business enterprises -- Law and legislation -- South Africa; Tax deductions -- South Africa; Contingent liabilities (Accounting) -- Taxation -- South Africa